2018
DOI: 10.1002/hyp.11455
|View full text |Cite
|
Sign up to set email alerts
|

Effects of rock fragment cover on hydrological processes under rainfall simulation in a semi‐arid region of China

Abstract: Rock fragment cover has long been an important agricultural crop production technique on the Loess Plateau, China. Although this approach plays an important role in controlling hydrological processes and preventing soil erosion, inconsistent results have been recovered in this field. In this study, we investigated the effects of rock fragment cover on infiltration, run‐off, soil erosion, and hydraulic parameters using rainfall simulation in the field in a semi‐arid region of China. Two field plots encompassing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
21
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 39 publications
(27 citation statements)
references
References 57 publications
2
21
0
Order By: Relevance
“…The calibrated Manning's roughness coefficient values were small but reasonable due to the low vegetation coverage and the large area of bare land and cultivated land in the Shejiagou catchment during the simulation period (i.e., 1964) [25,27]. Similar values have been measured on bare land and cultivated land through field experiments in the Loess Plateau in a few studies e.g., [51,52].…”
Section: Evaluation Criteriasupporting
confidence: 74%
“…The calibrated Manning's roughness coefficient values were small but reasonable due to the low vegetation coverage and the large area of bare land and cultivated land in the Shejiagou catchment during the simulation period (i.e., 1964) [25,27]. Similar values have been measured on bare land and cultivated land through field experiments in the Loess Plateau in a few studies e.g., [51,52].…”
Section: Evaluation Criteriasupporting
confidence: 74%
“…The calibrated Manning's roughness coefficient (n) values were small but reasonable due to the low vegetation coverage and the large area of bare land and cultivated land in the Shejiagou catchment during the simulation period (i.e., 1964) (Fang et al, 2011;Zhang et al, 2016). Similar values have been measured on bare land and cultivated land through field experiments in the Loess Plateau in a few studies (e.g., Wu et al, 2017;Xia et al, 2018). For example, Wu et al (2017) developed a sheet erosion equation for typical loess soil by conducting 36 plot experiments (rainfall intensity ranged from 48 to 150 mm h À1 , slopes ranged from 12.33% to 46.63%) and obtained the n-value range of 0.0102 to 0.0620 s m -1/3 .…”
Section: Calibration and Validationsupporting
confidence: 70%
“…Simanton and Toy [ 37 ] noted that hillslope morphology influenced rock fragment cover, finding a logarithmic increase of rock fragment cover with slope angle for hillslopes in semiarid range lands of Arizona, USA. Xia [ 38 ] found that rock fragments will be exposed on soil surface because of frequent human activities. Li et al [ 33 ] pointed out that the differences between the spatial patterns of rock fragment and vegetation coverage correlated with land use.…”
Section: Introductionmentioning
confidence: 99%